THE PROBLEMS AND SOLUTIONS OF TRAINING OF SPECIALISTS FOR INNOVATION ACTIVITIES IN THE SPHERE OF NUTRITION - Nikolay Viktorovich Gornikov; Sergey Vladimirovich Novoselov; Larisa Alexandrovna Mayurnikova; Natalia Ivanovna Davydenko (Современная наука и инновации, 2022)
The article describes the theoretical foundations of the system of training of specialists for the innovative activities on enterprises of food industry. Is presented systematization of the existing systems of training skilled frames and the role of innovation experts as a factor in the development of enterprises of nutrition sphere in the conditions of innovative activity.